The Effect of Entrepreneurial Knowledge and Environmental Support on Student Entrepreneurial Intention - Miswanto Miswanto; Shofia Suparti; Yanuar Rifqi Abdullah (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2020)
Abstract This study aims to examine the effect of entrepreneurial knowledge and environmental support on student entrepreneurship intentions. This study is a causal associative research with a quantitative approach. The variables of this study are entrepreneurial knowledge and environmental support as independent variables, entrepreneurship intentions as the dependent variable. This study is a research with 105 student respondents. Data collection techniques use questionnaire. Data analysis method used is regression. The results of this study indicate that (1) Entrepreneurial knowledge has a positive effect on entrepreneurial intentions and (2) Environmental support has a positive effect on entrepreneurial intentions. Therefore, the findings are that the knowledge and support of the environment has a positive effect on student entrepreneurship intentions.